Undang-undang Sultan Adam dalam Perspektif Politik Hukum Hindia-Belanda Pada Abad ke-18 dalam Penyusunan Hukum Positif di Indonesia - Ahmadi Hasan; Ali Mu’ammar (PT. Sharia Journal and Education Center, 2024)
Abstract This research explores the Sultan Adam Law (UUSA) in the Kingdom of Banjar during the Dutch colonization and the reign of Sultan Adam (1825-1857). UUSA, as a political law, reflects national law and the Shafi'i school of jurisprudence, despite being considered customary law. Islamic teachings, especially through UUSA and the Book of Sabilal Muhtadin, are integrated into customary law due to literacy limitations. Sultan Adam, through structural governance reforms, implemented Islamic principles in Banjar society, with UUSA serving as a crucial foundation. This research highlights the contribution of UUSA in depicting the integration of Islamic law in the Kingdom of Banjar and recognizes its historical impact in the study of customary law. Keywords: Sultan Adam, law, Banjar Abstrak Penelitian ini membahas Undang-Undang Sultan Adam (UUSA) di Kerajaan Banjar pada masa penjajahan Belanda dan pemerintahan Sultan Adam (1825-1857). UUSA, sebagai undang-undang politik, mencerminkan hukum nasional dan fikih mazhab Syafi'i, meskipun dianggap sebagai hukum adat. Ajaran Islam, terutama melalui UUSA dan Kitab Sabilal Muhtadin, terintegrasi dalam hukum adat karena keterbatasan literasi. Sultan Adam, melalui reformasi struktural pemerintahan, menerapkan prinsip-prinsip Islam dalam masyarakat Banjar, dengan UUSA menjadi landasan penting. Penelitian ini menyoroti kontribusi UUSA dalam menggambarkan integrasi hukum Islam dalam Kerajaan Banjar dan mengakui dampak historisnya dalam studi hukum adat. Kata Kunci: Sultan Adam, Hukum Banjar